Mathematical Problem-Solving Ability from Self-Regulated Learning for Class 10th Senior High School Students - Nurina Hidayah; Windi Dina Safitri; Zaenuri Zaenuri; Iwan Junaedi; Masrukhan Masrukhan (International Conference on Science, Education, and Technology, 2022)
There is a relationship between mathematical problem-solving ability and student self-regulated learning. Data collection using trigonometric comparison math problems and self-regulated learning questionnaires. The subjects in this study were students of class 10th at senior high school 1 Doro. They were taking research subjects based on the category of student self-regulated learning consisting of low, medium, and high levels. Data analysis techniques in this study are data reduction, data presentation, and conclusion drawing. Four indicators of problem-solving ability are used, including understanding the problem, designing problem-solving strategies, performing calculations, and looking back at the problem-solving results. The results indicate that students with a high level of self-regulated learning have problem-solving abilities that tend to be better. Students with high self-regulated learning can meet the indicators of problem-solving ability at the stage of understanding the problem. They are less able at stages to design problem-solving strategies and perform calculations. The finding is that the subject cannot meet the step of looking back on problem-solving. Second, students with moderate self-regulated learning have problem-solving abilities that tend to be quite good. Students in moderate self-regulated learning have not been fully able to meet the indicators of problem-solving ability in understanding the problem. They are unable to complete the other problem-solving stages. Third, students with low levels of self-regulated learning have problem-solving abilities that tend to be less good. Students in this category cannot meet the four indicators of problem-solving ability.